Current insights in the preclinical study of palatal wound healing and oronasal fistula after cleft palate repair - Chen, Jiali; Yang, Renjie; Yin, Jiayi; Shi, Bing; Huang, Hanyao (Frontiers in Cell and Developmental Biology, 2023)
Oronasal fistula (ONF) was the unfavorable prognosis of poor palatal wound healing after surgery, that can happen after cleft palate repair, Poor palatal wound healing after cleft palate repair could lead to unfavorable prognosis such as oronasal fistula (ONF), which might affect the patient's velopharyngeal function as well as their quality of life. Thus, avoiding the occurrence of ONF or restoring poor palatal wound healing for avoiding the occurrence of ONF should be considered the key to postoperative care after cleft palate repair. This review provided current insights in the preclinical study of ONF poor palatal wound healing after cleft palate repair. This review comprehensively introduced the animal model establishment for palatal wound healing and related ONF, including the models by mice, rats, piglets, and dogs, and then demonstrated the aspects for investigating poor palatal wound healing the cause of ONF and related treatments for ONF, including possible signaling pathways that could be involved in the formation of poor palatal wound healing ONF, the related microbiota changes because of the deformity of palatal structure, and the studies for potential therapeutic strategies for palatal wound healing and ONF. The purpose of this review was to show the state of the art in preclinical studies about palatal wound healing and ONF after cleft palate repair and to show the promising aspects for better management of palatal wound healing and ONF. Keywords mechanism; oronasal fistula; oral microflora; treatments; wound healing